2018
DOI: 10.22295/grifos.v27i45.4454
|View full text |Cite
|
Sign up to set email alerts
|

O Programa Nacional de Alimentação Escolar (PNAE) como mecanismo de política de inclusão na agricultura familiar do Nordeste do Brasil

Abstract: O objetivo é analisar a importância do Programa Nacional de Alimentação Escolar (PNAE) como mecanismo de inclusão e de política com foco na demanda, e explicar as transformações que o PNAE tem possibilitado na estrutura da agricultura familiar da região Nordeste do Brasil. Como metodologia, os dados utilizados no trabalho são de base secundária, extraídos dos sites do Instituto Nacional de Estudos e Pesquisa Educacionais Anísio Teixeira (INEP), do Fundo Nacional de Desenvolvimento da Educação (FNDE) e do Porta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
0
5
0
8
Order By: Relevance
“…The South region of the country had the highest percentage of cities that bought food from family farming (71.3%), and the Midwest had the lowest (35.3%) (Saraiva et al, 2013). Nunes et al (2018) verified an evolution in the percentage of acquisition of products from family farming in the Northeast region, migrating from 7% in 2011 to 20% in 2015. Although the region is not reaching the required minimum, being the second with a lower percentage of acquisition between the years mentioned, it was observed that the number of municipalities doubled concerning 2011.…”
Section: Overview Of Supply and Demand Between Family Farming Productmentioning
confidence: 77%
See 3 more Smart Citations
“…The South region of the country had the highest percentage of cities that bought food from family farming (71.3%), and the Midwest had the lowest (35.3%) (Saraiva et al, 2013). Nunes et al (2018) verified an evolution in the percentage of acquisition of products from family farming in the Northeast region, migrating from 7% in 2011 to 20% in 2015. Although the region is not reaching the required minimum, being the second with a lower percentage of acquisition between the years mentioned, it was observed that the number of municipalities doubled concerning 2011.…”
Section: Overview Of Supply and Demand Between Family Farming Productmentioning
confidence: 77%
“…Even so, it is emphasized that the PNAE has conquered a critical role to guarantee the flow of production, enabling a significant opening of the vision of family farmers to a market niche whose dimension was previously unknown (Nunes et al, 2018). However, despite advances in recent years, gaps still exist that limit the effectiveness of the program, which comprise the intended impacts and the real impacts generated by the implementation of the policy.…”
Section: Overview Of Supply and Demand Between Family Farming Productmentioning
confidence: 99%
See 2 more Smart Citations
“…O Programa Nacional de Alimentação Escolar (PNAE), como mecanismo de política pública, busca afirmar o papel da agricultura familiar e reconhecer que os agricultores familiares têm capacidade coletiva para produzir alimentos de qualidade, bem como condições de participar da comercialização direta dos seus produtos, além de estimular a interação entre oferta e demanda de produtos da agricultura familiar por meio dos recursos disponíveis para as escolas (Nunes, de Morais, de Aquino, & Gurgel, 2018). Research, Society and Development, v. 9, n. 10, e8599109201, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.9201 O artigo 14, da Lei nº 11.947/2009 tornou obrigatória à aplicação mínima de 30% dos recursos repassados pelo Fundo Nacional de Desenvolvimento da Educação (FNDE) aos municípios para compra de alimentos da agricultura familiar (Brasil, 2009).…”
Section: Introductionunclassified